Barriers to the Rural Women Empowerment - Arun Kumar , Prakash Singh , R. P. Sahu , Khushbu Singh , Ram Jiyawan; Pawan kumar (Indian Journal of Extension Education, 2014)
The study was conducted in 2011 among SHGs in Faizabad district of Uttar Pradesh. A total of 120 respondents (60 members from SHG and 60 members from no- SHG of dairy enterprise were selected purposively for the study . The study aimed at analyzing the on barriers of rural women empowerment. Majority of the SHG and non-SHG members faced the barriers as lack of education, negative social attitude about women’s role outside the home, illiteracy among women, lack of cooperation, lack of leadership and lack of information about banking procedures etc. There were some suggestions perceived by the majority of SHG and non SHG members of dairy enterprise such as education to the women should be provided free of cost, extension personnel should create an interest in forming of SHG among rural members for their active participation, skill oriented training programme for SHG members should be initiated by the government, financial support should be strong for SHG members and women can be protected outside home by establishing the strong punishment/ rules.